2017
DOI: 10.1371/journal.pone.0160617
|View full text |Cite
|
Sign up to set email alerts
|

Knoetschkesuchus langenbergensis gen. nov. sp. nov., a new atoposaurid crocodyliform from the Upper Jurassic Langenberg Quarry (Lower Saxony, northwestern Germany), and its relationships to Theriosuchus

Abstract: We report a new, small-sized atoposaurid crocodyliform from the Upper Jurassic of Langenberg, Northeastern Germany. Atoposaurids are small-sized Mesozoic crocodyliforms of mainly European distribution, which are considered to be phylogenetically close to the origin of Eusuchia. Knoetschkesuchus langenbergensis gen. nov. sp. nov. is represented by two well-preserved skulls and additional cranial and postcranial remains representing different ontogenetic stages. 3D reconstructions of a juvenile skull based on mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 43 publications
1
37
0
Order By: Relevance
“…We tentatively identify DfMMh/FV1/19 as belonging to a theropod dinosaur. Unfortunately, unguals of alternative taxa, such as crocodiles, lizards, and testudinids, all groups for which fossils have been found and described from the Langenberg Quarry (Thies, Windorf & Mudroch, 1997;Karl et al, 2006;Karl et al, 2008;Jansen & Klein, 2013;Richter et al, 2013;Schwarz et al, 2017), are even less described in the literature than theropod unguals, so that the following comments are largely based on personal observations. Testudinid taxa that appear in the Lower Saxony Basin, including the Langenberg Quarry (e.g.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We tentatively identify DfMMh/FV1/19 as belonging to a theropod dinosaur. Unfortunately, unguals of alternative taxa, such as crocodiles, lizards, and testudinids, all groups for which fossils have been found and described from the Langenberg Quarry (Thies, Windorf & Mudroch, 1997;Karl et al, 2006;Karl et al, 2008;Jansen & Klein, 2013;Richter et al, 2013;Schwarz et al, 2017), are even less described in the literature than theropod unguals, so that the following comments are largely based on personal observations. Testudinid taxa that appear in the Lower Saxony Basin, including the Langenberg Quarry (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…Among them are the only known Jurassic mammals from Germany, the pinheirodontid multituberculate Teutonodon langenbergensis (Martin et al, 2016), the paulchoffatiid multituberculate Cimbriodon multituberculatus (Martin et al, 2019), and the large morganucodontan mammaliaform Storchodon cingulatus (Martin et al, in press). Additionally, a threedimensionally preserved articulated skeleton of a small pterosaur (Fastnacht 2005), teeth and skeletons of the small non-marine atoposaurid crocodilian Knoetschkesuchus langenbergensis (Schwarz et al 2017), various remains of marine crocodylians (Karl et al, 2006;2008) and the partial skeleton of a paramacellodid lizard (Richter et al 2013) have been reported. Diverse marine turtle material (including several skulls) comprises cf.…”
Section: Fossil Vertebrates From the Langenberg Quarrymentioning
confidence: 99%
“…Among them are the only known Jurassic mammals from Germany, the pinheirodontid multituberculate Teutonodon langenbergensis (Martin et al, 2016), the paulchoffatiid multituberculate Cimbriodon multituberculatus (Martin et al, 2019a), and the large morganucodontan mammaliaform Storchodon cingulatus (Martin et al, 2019b). Additionally, a three-dimensionally preserved articulated skeleton of a small pterosaur (Fastnacht, 2005), teeth and skeletons of the small non-marine atoposaurid crocodilian Knoetschkesuchus langenbergensis (Schwarz, Raddatz & Wings, 2017), various remains of marine crocodylians (Karl et al, 2006;Karl et al, 2008) and the partial skeleton of a paramacellodid lizard (Richter et al, 2013) have been reported. Diverse marine turtle material (including several skulls) comprises cf.…”
Section: Fossil Vertebrates From the Langenberg Quarrymentioning
confidence: 99%
“…However, the various phylogenetic analyses appear to converge on a divergence between the large-bodied and primarily aquatic neosuchian clades (Pholidosauridae þ Dyrosauridae) and the relatively smaller-bodied, terrestrial or semi-aquatic clades (although the position of Goniopholididae is variable; Adams 2014; Turner 2015; Young et al 2016b;Schwarz et al 2017). Yet little is known about neosuchians before the Late Jurassic due to a patchy non-marine fossil record (Mannion et al 2015;Tennant et al 2016b).…”
Section: Implications Of Nms G2016211 As a Potential Hylaeochampsidmentioning
confidence: 99%